Teknik Jitu Menjadi Marketer di Era Digital: Peluang Kerja Baru di Dunia Cyber Digital - Salahudin, Salahudin; Prisgunanto, Ilham (Jurnal Pengabdian Kepada Masyarakat Kalam, 2025)
Marketing is sometimes perceived as straightforward and can be executed haphazardly. However, digital-era marketing is highly complex and requires integrity and ethical conduct. The days of marketing through deception and misleading the public are long gone. In the cyber-digital era, marketing has become increasingly significant in relation to societal economic behavior. The seminar titled “Digital Marketing in the Millennial 4.0 Era: Effective Techniques for Becoming a Digital Marketer,” organized by the Advertising Program at Muhammadiyah University of Tangerang, aims to help graduating students from the Advertising Program at Muhammadiyah University of Tangerang understand the significance of information and the digital world, as well as the importance of digital ethics. The seminar, attended by 50 prospective graduates, focused on their readiness and understanding of cyber digital marketing. Based on the results of the pretest and post-test, there was a significant change of 2.61 in the average responses of participants using the Likert scale. The conclusion can be understood as honesty, sincerity, and nobility being the foundation of relationships in the internet network, returning humans to their humanity rather than mere lifeless accounts. The success of marketing communication lies in the innovation and creativity of individuals in conducting economic activities.